Step
*
1
1
1
1
1
1
1
of Lemma
coW-wfdd_functionality
1. A : 𝕌'
2. B : A ⟶ Type
3. w : coW(A;a.B[a])
4. w' : coW(A;a.B[a])
5. p : n:ℕ ⟶ copath(a.B[a];w')
6. ∀i:ℕ
     ((copath-length(p i) = i ∈ ℤ) 
⇒ (copath-length(p (i + 1)) = (i + 1) ∈ ℤ) 
⇒ copathAgree(a.B[a];w';p i;p (i + 1)))
7. q : ℕ ⟶ copath(a.B[a];w)
8. ∀n:ℕ. ((∀i:ℕn. (copath-length(q i) = i ∈ ℤ)) 
⇒ (∀i:ℕn - 1. copathAgree(a.B[a];w;q i;q (i + 1))))
9. ∀n:ℕ
     ((∀i:ℕn. (copath-length(p i) = i ∈ ℤ))
     
⇒ (∀i:ℕn. ((copath-length(q i) = i ∈ ℤ) ∧ coW-equiv(a.B[a];copath-at(w;q i);copath-at(w';p i)))))
10. i : ℕ
11. copath-length((λn.if bdd-all(n + 1;i.(copath-length(q i) =z i)) then q n else () fi ) i) = i ∈ ℤ
12. copath-length((λn.if bdd-all(n + 1;i.(copath-length(q i) =z i)) then q n else () fi ) (i + 1)) = (i + 1) ∈ ℤ
13. ↑bdd-all(i + 1;i.(copath-length(q i) =z i))
14. ↑bdd-all((i + 1) + 1;i.(copath-length(q i) =z i))
⊢ copathAgree(a.B[a];w;q i;q (i + 1))
BY
{ ((RWO "assert-bdd-all" (-1) THENA Auto) THEN (RW assert_pushdownC (-1) THENA Auto)) }
1
1. A : 𝕌'
2. B : A ⟶ Type
3. w : coW(A;a.B[a])
4. w' : coW(A;a.B[a])
5. p : n:ℕ ⟶ copath(a.B[a];w')
6. ∀i:ℕ
     ((copath-length(p i) = i ∈ ℤ) 
⇒ (copath-length(p (i + 1)) = (i + 1) ∈ ℤ) 
⇒ copathAgree(a.B[a];w';p i;p (i + 1)))
7. q : ℕ ⟶ copath(a.B[a];w)
8. ∀n:ℕ. ((∀i:ℕn. (copath-length(q i) = i ∈ ℤ)) 
⇒ (∀i:ℕn - 1. copathAgree(a.B[a];w;q i;q (i + 1))))
9. ∀n:ℕ
     ((∀i:ℕn. (copath-length(p i) = i ∈ ℤ))
     
⇒ (∀i:ℕn. ((copath-length(q i) = i ∈ ℤ) ∧ coW-equiv(a.B[a];copath-at(w;q i);copath-at(w';p i)))))
10. i : ℕ
11. copath-length((λn.if bdd-all(n + 1;i.(copath-length(q i) =z i)) then q n else () fi ) i) = i ∈ ℤ
12. copath-length((λn.if bdd-all(n + 1;i.(copath-length(q i) =z i)) then q n else () fi ) (i + 1)) = (i + 1) ∈ ℤ
13. ↑bdd-all(i + 1;i.(copath-length(q i) =z i))
14. ∀i:ℕ(i + 1) + 1. (copath-length(q i) = i ∈ ℤ)
⊢ copathAgree(a.B[a];w;q i;q (i + 1))
Latex:
Latex:
1.  A  :  \mBbbU{}'
2.  B  :  A  {}\mrightarrow{}  Type
3.  w  :  coW(A;a.B[a])
4.  w'  :  coW(A;a.B[a])
5.  p  :  n:\mBbbN{}  {}\mrightarrow{}  copath(a.B[a];w')
6.  \mforall{}i:\mBbbN{}
          ((copath-length(p  i)  =  i)
          {}\mRightarrow{}  (copath-length(p  (i  +  1))  =  (i  +  1))
          {}\mRightarrow{}  copathAgree(a.B[a];w';p  i;p  (i  +  1)))
7.  q  :  \mBbbN{}  {}\mrightarrow{}  copath(a.B[a];w)
8.  \mforall{}n:\mBbbN{}.  ((\mforall{}i:\mBbbN{}n.  (copath-length(q  i)  =  i))  {}\mRightarrow{}  (\mforall{}i:\mBbbN{}n  -  1.  copathAgree(a.B[a];w;q  i;q  (i  +  1))))
9.  \mforall{}n:\mBbbN{}
          ((\mforall{}i:\mBbbN{}n.  (copath-length(p  i)  =  i))
          {}\mRightarrow{}  (\mforall{}i:\mBbbN{}n.  ((copath-length(q  i)  =  i)  \mwedge{}  coW-equiv(a.B[a];copath-at(w;q  i);copath-at(w';p  i)))))
10.  i  :  \mBbbN{}
11.  copath-length((\mlambda{}n.if  bdd-all(n  +  1;i.(copath-length(q  i)  =\msubz{}  i))  then  q  n  else  ()  fi  )  i)  =  i
12.  copath-length((\mlambda{}n.if  bdd-all(n  +  1;i.(copath-length(q  i)  =\msubz{}  i))  then  q  n  else  ()  fi  )  (i  +  1))
=  (i  +  1)
13.  \muparrow{}bdd-all(i  +  1;i.(copath-length(q  i)  =\msubz{}  i))
14.  \muparrow{}bdd-all((i  +  1)  +  1;i.(copath-length(q  i)  =\msubz{}  i))
\mvdash{}  copathAgree(a.B[a];w;q  i;q  (i  +  1))
By
Latex:
((RWO  "assert-bdd-all"  (-1)  THENA  Auto)  THEN  (RW  assert\_pushdownC  (-1)  THENA  Auto))
Home
Index